A preliminary study of human amniotic membrane as a potential chondrocyte carrier - Boo, L.; Sofiah, S.; Selvaratnam, L.; Tai, C.C.; Pingguan-Murphy, Belinda; Kamarul, Tunku (University of Malaya, 2009)
Purpose: To investigate the feasibility of using processed human amniotic membrane (HAM) to support the attachment and proliferation of chondrocytes in vitro which in turn can be utilised as a cell delivery vehicle in tissue engineering applications. Methods: Fresh HAM obtained from patients undergoing routine elective caesarean sections was harvested, processed and dried using either freeze drying (FD) or air drying (AD) methods prior to sterilisation by gamma irradiation. Isolated, processed and characterised rabbit autologous chondrocytes were seeded on processed HAM and cultured for up to three weeks. Cell attachment and proliferation were examined qualitatively using inverted brightfield microscopy. Results: Processed HAM appeared to allow cell attachment when implanted with chondrocytes. Although cells seeded on AD and FD HAM did not appear to attach as strongly as those seeded on glycerol preserved intact human amniotic membrane, these cells to be proliferated in cell culture conditions. Conclusion: Preliminary results show that processed HAM promotes chondrocyte attachment and proliferation.